Draw 50 cats - Ames, Lee J. (Garden City, N.Y. : Doubleday, 1986)
Step-by-step instructions on how to draw a variety of cats, including domestic breeds, wild cats, cuddly kittens, and celebrity cats.
Children's Catalog (Wilson)
Junior High School Library Catalog (Wilson)
Booklist
6.1
5-8
Keywords: Cats in art -- Juvenile literature; Drawing -- Technique -- Juvenile literature; Cats in art; Drawing -- Technique; Cats in art; Drawing -- Technique